How fit are children and adolescents with haemophilia in Germany? Results of a prospective study assessing the sport‐specific motor performance by means of modern test procedures of sports science. (4th February 2015) - Seuser, A.; Boehm, P.; Ochs, S.; Trunz‐Carlisi, E.; Halimeh, S.; Klamroth, R.
Summary There are a lot of publications on the physical fitness of patients with haemophilia (PWH), however, most studies only reflect individual sport‐specific motor capacities or focus on a single fitness ability. They involve small patient populations. In this respect principal objective of this study was to compare the physical fitness in all respects and the body composition of young PWH to healthy peers based on the most valid data we could get. Twenty‐one German haemophilia treatment centres were visited from 2002 to 2009. PWH between 8 and 25 years were included. They performed a five‐stage fitness test covering the sport‐specific motor capacities for coordination, measured by one leg stand, strength, aerobic fitness and mobility as well as body composition. The patients' results were compared with age‐ and gender‐specific reference values of healthy subjects. Two hundred and eighty‐five PWH (mean age 13.2 ± 4.5 years, 164 PWH with severe disease) were included prospectively in the study. PWH are significantly below the reference values of healthy subjects in the one‐leg stand test, the mobility of the lower extremity, the strength ratio of chest and back muscles and the endurance test. In body composition, the back strength and the mobility of the upper extremity PWH are significantly above the reference values. There are no significant differences in abdominal strength. In conclusion we found specific differences in different fitness abilities between PWH and healthy subjects. Knowing this, we are able to work out exercise programmes to compensate the diminished fitness abilities for our PWH.